Efektivitas Pengawasan Pelaksanaan Pekerjaan pada Dinas Pekerjaan Umum dan Penataan Ruang Kabupaten Ogan Komering Ilir - Yanto, Budi Apri; Syuroh, Mat; Saswita, Saswita (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2026)
The purpose of this study was to analyze the effectiveness of supervising work implementation at the Public Works and Spatial Planning (PUPR) Office of Ogan Komering Ilir (OKI) Regency. This research is a descriptive research with a qualitative approach. The type of data used is based on quantitative data and qualitative data, while the sources are based on primary data and secondary data. Observations, interviews and documentation are used as data collection tools. The informants in this study were the Head of the Bina Marga Division of the Public Works and Spatial Planning Office of OKI Regency; Head of the Quality Control Section for the Technical Supervision of the Public Works and Spatial Planning Office of OKI Regency; Head of Technical Supervision Section for Technical Supervision of Public Works and Spatial Planning Office of OKI Regency; Head of the Evaluation and Monitoring Section for the Technical Supervision Sector of the Public Works and Spatial Planning Office of OKI Regency; The contractor for the implementation of the work of the OKI Regency Office of Public Works and Spatial Planning; and Consultants/supervisory team for the implementation of the work of the Office of Public Works and Spatial Planning of OKI Regency. Data analysis is a qualitative analysis with an interactive model. Based on the research results, it is known that the Supervision of Work Implementation at the Office of Public Works and Spatial Planning in Ogan Komering Ilir Regency has not been effective.